2022
DOI: 10.3390/jcm11133789
|View full text |Cite
|
Sign up to set email alerts
|

A Scoring System for Predicting Microvascular Invasion in Hepatocellular Carcinoma Based on Quantitative Functional MRI

Abstract: Microvascular invasion (MVI) in hepatocellular carcinoma (HCC) is a histopathological marker and risk factor for HCC recurrence. We integrated diffusion-weighted imaging (DWI) and magnetic resonance (MR) image findings of tumors into a scoring system for predicting MVI. In total, 228 HCC patients with pathologically confirmed MVI who underwent surgical resection or liver transplant between November 2012 and March 2021 were enrolled retrospectively. Patients were divided into a right liver lobe group (n = 173, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Chawla et al 84 combined median ADC and dynamic contrast-enhanced (DCE) MRI parameters and distinguished chemoradiation responders from nonresponders among patients with head and neck squamous cell carcinoma, with an AUC of 0.85. For predicting microvascular invasion of hepatocellular carcinoma, which is an adverse prognostic factor, Liao et al 85 and Wang et al 86 reported high predictive values of multiparametric MRI using multivariate logistic regression analyses. The AUC was 0.84 with the model using tumor size (≥3 cm), single tumor involving more than 2 segments, mean ADC, and minimum ADC in the study by Liao et al, 85 whereas the AUC was 0.784 by combining mean kurtosis and irregular circumferential enhancement in the study by Wang et al 86 Another machine learning study with linear discrimination analysis utilized T1, T2, and proton density values acquired with QRAPMASTER extracted from gray matter, white matter, and lesion masks 87 .…”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chawla et al 84 combined median ADC and dynamic contrast-enhanced (DCE) MRI parameters and distinguished chemoradiation responders from nonresponders among patients with head and neck squamous cell carcinoma, with an AUC of 0.85. For predicting microvascular invasion of hepatocellular carcinoma, which is an adverse prognostic factor, Liao et al 85 and Wang et al 86 reported high predictive values of multiparametric MRI using multivariate logistic regression analyses. The AUC was 0.84 with the model using tumor size (≥3 cm), single tumor involving more than 2 segments, mean ADC, and minimum ADC in the study by Liao et al, 85 whereas the AUC was 0.784 by combining mean kurtosis and irregular circumferential enhancement in the study by Wang et al 86 Another machine learning study with linear discrimination analysis utilized T1, T2, and proton density values acquired with QRAPMASTER extracted from gray matter, white matter, and lesion masks 87 .…”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%
“…For predicting microvascular invasion of hepatocellular carcinoma, which is an adverse prognostic factor, Liao et al 85 and Wang et al 86 reported high predictive values of multiparametric MRI using multivariate logistic regression analyses. The AUC was 0.84 with the model using tumor size (≥3 cm), single tumor involving more than 2 segments, mean ADC, and minimum ADC in the study by Liao et al, 85 whereas the AUC was 0.784 by combining mean kurtosis and irregular circumferential enhancement in the study by Wang et al 86 Another machine learning study with linear discrimination analysis utilized T1, T2, and proton density values acquired with QRAPMASTER extracted from gray matter, white matter, and lesion masks. 87 They used mean values of these masks to differentiate between multiple sclerosis, a demyelinating disorder of the central nervous system, and hereditary diffuse leukoencephalopathy with spheroids, a rare demyelinating disorder that can sometimes be misdiagnosed as multiple sclerosis.…”
Section: Analyzing Multiparametric Mr Imagesmentioning
confidence: 99%